Development of the Siak Library and Archives Service (2004-2022) - Yuliana, Fitri Iska; Bunari, Bunari; Fikri, Asyrul (CV. Rayyan Dwi Bharata, 2024)
This research discusses the history and development of the Siak Regency Library and Archives Service as one of the libraries that is very active and accomplished in carrying out its role in Siak Regency. The purpose of this research is to find out the history of the formation of the Siak Library and Archives Service, examine the development of the Siak Library and Archives Service in 2004-2022, be able to provide an overview of how the Siak library and archives collection is managed, and be able to find out the use of the Siak Library and Archives Service in carrying out its duties. The method used is a historical method which includes heuristic, verification, interpretation and historiography stages. The results of the research show that the formation of the Siak Library and Archives Service was due to input from the community to make the library, which was originally a regional secretariat library which at that time could only be accessed by government employees, into a public library so that the general public in Siak could access the library. Since its initial formation in 2004-2022, the Siak Library and Archives Service has experienced developments in various aspects, including infrastructure, library collections, library services and library visitors, up to the use of the Siak Library and Archives Service as a learning resource and also a source of history.